Role of isoflavones and its derivatives on the growth of Pseudomonas putida and Escherichia coli - Daniel, V; Srinivas, P; Santhosh kumar, K; Krupadanam, D (Journal of Phytology, 2012)
Two naturally occurring isoflavones genistine and biochanin - A, and their dihydro derivatives (isoflavones) as well as nine perhydroginated isoflavones (isoflavanes) were tested for their effects on mycelial growth of two soil bacteria viz., Pseudomonas putida and Escherichia coli. All the isoflavonenoids of the biochanin - A series showed the genistine isoflavane and the other isoflavanes with two hydroxyl groups and one methoxy groups are toxic, while isoflavones with two and one methoxy group were almost inactive. Genistein, a radio protective soy isoflavone and protein kinase inhibitor, blocks the invasion of pathogenic bacteria in mammalian epithelial cells. The purpose of this study was to evaluate the direct effect of genistein on the survival and growth of the probiotic Lactobacillus reuteri and selected opportunistic bacteria in vitro as a prelude to in vivo use for managing post irradiation sepsis. The opportunistic bacterial enteropathogens viz., Escherichia coli, Shigella sonnei, and Staphylococcus aureus as well as Klebsiella pneumoniae and the non-pathogenic organism, Bacillus anthracis (Sterne) were evaluated. The latter two bacteria are found in the environment and may be of concern in irradiated individuals. A standard in vitro test was employed to evaluate the direct effect of genistein on the bacteria.